2022
DOI: 10.1038/s44184-022-00015-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of limiting digital screen use on well-being, mood, and biomarkers of stress in adults

Abstract: Studies have linked higher digital screen use with poorer mental health. However, there is limited experimental evidence to suggest a causal relationship. In this trial, we aimed to investigate the effects of limiting recreational digital screen use on mental well-being, mood, and biomarkers of stress in healthy young and middle-aged adults. We randomly allocated 89 families (including 164 adults) to participate in an extensive screen media reduction intervention or control. Participants in the intervention gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…This study is a prespecified secondary analysis of the SCREENS (Short-term Efficacy of Reducing Screen-Based Media Use) trial, which is a parallel cluster randomized clinical trial (study protocol available in Supplement 1). Results for the primary outcome of the SCREENS trial and a secondary analysis have previously been reported . The primary outcome analysis revealed that children and adolescents allocated to the screen media reduction group increased their nonsedentary leisure time by 45 minutes per day compared with children and adolescents in the control group .…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…This study is a prespecified secondary analysis of the SCREENS (Short-term Efficacy of Reducing Screen-Based Media Use) trial, which is a parallel cluster randomized clinical trial (study protocol available in Supplement 1). Results for the primary outcome of the SCREENS trial and a secondary analysis have previously been reported . The primary outcome analysis revealed that children and adolescents allocated to the screen media reduction group increased their nonsedentary leisure time by 45 minutes per day compared with children and adolescents in the control group .…”
Section: Methodsmentioning
confidence: 84%
“…40,41 A possible explanation of the positive effects found among both children and adolescents could be that parents participating in the SCREENS trial also reported improved mental well-being (WHO-5 Well-being Index score), as reported previously. 25 The positive effects may also be explained by increases in shared leisure time among family members without use of screen media devices during the intervention, potentially making room for more social interactions. Reduced interpersonal engagement could heighten emotional symptoms, manifesting as amplified feelings of isolation, loneliness, and social anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a prior analysis, the authors showed that parental mood also improved. 3 The authors, however, did not investigate in the present study whether this parental mood change accounted for the observed improvement in children's psychiatric problems.…”
mentioning
confidence: 71%
“…And it might make the parents, if not the children, happier. As already mentioned, the parents in this trial also had to hand in their smartphones, the positive effect on parental mental health was just as substantial in parents as in children, and it was the parents who evaluated the mental health of their children in this study.…”
mentioning
confidence: 90%